‘‘Pancada de amor não dói”: a audiência de custódia e a visibilidade invertida da vítima nos casos de violência doméstica / “Love battering doesn’t hurt: the initial appearance upon arrest and the victim's reversed visibility in cases of domestic violence" - Valença, Manuela Abath; Mello, Marilia Montenegro Pessoa de (Revista Direito e Práxis, 2020)
DOI: 10.1590/2179-8966/2020/50471 Resumo Este trabalho, fruto de uma pesquisa empírica realizada em audiências de custódias no Recife e em Olinda, problematiza a ausência da vítima nos casos da Lei Maria da Penha nesses atos. Para tanto, confrontamos a atuação dos/as juízes/as da audiência de custódia ao posicionamento do Supremo Tribunal Federal, na ADI 4424, que negou, em nome da proteção às mulheres, a representação no crime de lesão corporal leve nos casos abrangidos pela Lei Maria da Penha. Durante a pesquisa percebemos que, o “batedor de mulher”, ao dividir, nas audiências, espaço com “ladrões” e “traficantes”, esvazia a gravidade da violência doméstica, gerando decisões liberatórias que, não são necessariamente um problema em si, mas podem se tornar quando não acompanhadas de uma assistência específica à vítima. Ao final, mesmo apontando um caminho de muitas dificuldades, propomos um diálogo entre a Lei Maria da Penha e as audiências de custódia para minorar a revitimização da mulher no processo penal. Palavras-chave: Audiência de custódia; Violência doméstica contra a mulher; Revitimização. Abstract This article draws on findings of an empirical research on the so-called “custody hearings”, that is, the initial appearance before a judge after detainees are arrested for a crime in Brazil. This study was carried out in the cities of Recife and Olinda and the aim in this paper is to problematise the absence of the victim at such hearings in cases ruled by Brazil’s domestic violence law – the ‘Maria da Penha Law’. In this vein, we confronted judges’ workings in custody hearings against the backdrop of a decision made by Brazil’s Supreme Federal Court, in the “ADI 4424” case, which imposed “obligation to prosecute” domestic abuse assaults causing minor physical injuries – all in name of protecting the victim. During the research fieldwork we found that the seriousness of domestic violence is somewhat undercut for “women batterers” share the same space as “thieves” and “drug dealers” in the workings of custody hearings. This has led to decisions to release defendants from detention when their cases fall under the auspices of the Maria da Penha Law. This is not a problem in itself but may well become one when victims are left unassisted. At the end of the day, while acknowledging its many challenges, we suggest a dialogue between the Maria da Penha Law and custody hearings to lessen the revictimization of women in criminal proceedings in Brazil. Keywords: Custody hearings; Domestic violence against women; Revictimisation.